2010
DOI: 10.1080/00140130903194138
|View full text |Cite
|
Sign up to set email alerts
|

A performance improvement case study in aircraft maintenance and its implications for hazard identification

Abstract: Aircraft maintenance is a highly regulated, safety critical, complex and competitive industry. There is a need to develop innovative solutions to address process efficiency without compromising safety and quality. This paper presents the case that in order to improve a highly complex system such as aircraft maintenance, it is necessary to develop a comprehensive and ecologically valid model of the operational system, which represents not just what is meant to happen, but what normally happens. This model then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 9 publications
(6 reference statements)
0
37
0
1
Order By: Relevance
“…− Techninės priežiūros vykdymo sistema -šioje sistemoje atliekamas pagrindinis darbas. Nepaisant atliekamų darbų apimties, visi procesai ir operacijos vykdomos prižiūrint gamybos, planavimo, komercijos ir kokybės skyriams (Ward et al 2012). L. Baronienė (2006) teigia, kad sisteminis požiūris suteikia organizacijai galimybę rezultatyviai ir efektyviai siekti tikslų, nes visi tarpusavyje susiję procesai suprantami ir valdomi kaip sistema.…”
Section: įVadasunclassified
“…− Techninės priežiūros vykdymo sistema -šioje sistemoje atliekamas pagrindinis darbas. Nepaisant atliekamų darbų apimties, visi procesai ir operacijos vykdomos prižiūrint gamybos, planavimo, komercijos ir kokybės skyriams (Ward et al 2012). L. Baronienė (2006) teigia, kad sisteminis požiūris suteikia organizacijai galimybę rezultatyviai ir efektyviai siekti tikslų, nes visi tarpusavyje susiję procesai suprantami ir valdomi kaip sistema.…”
Section: įVadasunclassified
“…Dignity and trust in relations within organizations appear to play a critical role in enabling change and improvement to happen. Following a meta-analysis of three large scale ergonomics / human factor interventions in aircraft maintenance organizations Ward [45] found that organizational change was not possible when people were not being treated with dignity in the first instance. She found that resistance behaviors were not objections to change per se but to how people were being treated at the time and were what Hosking [15] terms 'the local rational response'.…”
Section: The Role Of Culturementioning
confidence: 99%
“…She found that resistance behaviors were not objections to change per se but to how people were being treated at the time and were what Hosking [15] terms 'the local rational response'. Ward [45] demonstrated the importance of understanding the systemic basis of trust in change initiatives -in particular the existence of common goals, open communication, clearly understood ways of working (formal rules or procedures and normal ways of working being not too different) and having an opportunity for feedback and review. A history of mistrust also carries forward into current relationships.…”
Section: The Role Of Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Aircraft maintenance is a critical link to achieving this proactive safety culture and is a dynamic, highly regulated, safety critical and complex industry, often regulated by legally binding procedures and documentation. Similar to the RAN, designers and maintainers face unprecedented challenges from customers to increase their reliability (Ward et al, 2010). While facing these challenges, safety remains paramount.…”
Section: Commercial Insightmentioning
confidence: 99%